"Amoraic Baraitot" Reconsidered: The Case of Tannei Tanna Kameh. Issue 1 (12th May 2015) - Cohen, Barak S.
Abstract : Earlier scholars typically considered the tannaitic traditions transmitted by Amoraim in the two Talmuds to be later amoraic (largely Babylonian) creations. This supposition was based on a range of formalistic considerations: the introductory terms, the attitude of the Amoraim to their halakhic content, and the lack of parallels in tannaitic literature. A study of the approximately 140 baraitot introduced by the term "a Tanna taught in front of so-and-so" offers substantial critique of this supposition, which was often based on incorrect a priori assumptions or on faulty interpretations of sources. Assessment of the nature and origins of the halakhic content of these so-called "amoraic baraitot" requires thorough analysis of the halakhic traditions found in this collection and their comparison with parallels in Palestinian tannaitic literature.